Chartres et sa proche campagne au haut Moyen Age (fin Ve – fin Xe siècle). Topographie urbaine et péri-urbaine, analyse de structures et étude du mobilier : un premier bilan - Cyrille Ben Kaddour (Revue Archéologique du Centre de la France)
Since the nineteenth century, numerous archaeological investigations have been made on the territory of Chartres. If majority of excavations, diagnostics and incidental findings concerning the remains of Roman antiquity, some sites delivered evidences of the early Middle Ages (late Vth to late IXth century). There are essentially peri-urban settlement structures and funerary structures (small groups of graves and necropolis). However, these data were often undevelopped and published seldomly. This is an opportunity to evaluate knowledge about the city of Chartres in the early Middle Ages: appearance of the city, its evolution between Antiquity and Middle Ages, aspects of daily life and funerary practices through structures and materials found during the investigations. Although many obstacles to a real synthesis exist (little detailed studies of dark earth, funerals deposits, human bones and few 14C dating), archaeological data provide informations on the urban development of Chartres in early Middle Ages with regards to: withdrawal of the urban fabric, lack of defined boundaries of urbanized areas, reorganization resulting from the creation of Christian Holy places and burial spaces.